Antitermite Characteristics of Insecticides I- Results of Field Experiments Using Commercial Sample of Shell Liquid of Anacardium Occidentale, Aldrin and Dieldrin - Chatterjee, P. N.; Sen-Sarma, P. K. (Indian Forester, 1963)
Comparative prophylactic antitermite efficacy of three insecticides, viz., commerical sample of cashew nut shell liquid, Aldrin and Dieldrin was tested for a period of four years. The result shows that both Aldrin and Dieldrin in 1 % and 2% concentration behave satisfactorily for prophylactic protection of timbers against subterranean wood-destroying termites. But highest preference should be given to Aldrin at 2% concentration. Commercial sample of cashew nut shell liquid gave only little protection in the first and second year.